The degree of teachers' commitment to the ethics of the Code of Conduct from the point of view of principals in the Governorate of Aqaba - Abou Hamdy, Elham Nayef (Journal of Educational and Psychological Sciences, 2018)
The study aimed to determine the degree of commitment of teachers to the ethics of the Code of Conduct from the point of view of principals in the Governorate of Aqaba, and the descriptive descriptive approach was used for its purposes. The sample of the study is (56) managers and directors; they are all principals and principals of public schools in the city of Aqaba. The results of the study indicate that the commitment of teachers to the ethics of the Code of Conduct from the point of view of the principals in the Governorate of Aqaba obtained a total average (4.2) ie, high degree, while the sub-fields, the field of dealing with colleagues ranked first with an average (4.27) , And the second area of ​​dealing with managers with an average (4.17). (4.15). In the fourth place is the area of ​​teacher duties (4.15). Finally, the field of maintaining public money and the interests of the school and its property is average (4.09), all of which are highly rated. The results of the study showed that there are statistically significant differences at the level of (α = 0.05) to the degree of teachers' commitment to the ethics of the code of functional behavior due to gender variables. In light of the results of the study, a number of recommendations and proposals were presented to improve the level of teachers' commitment to the ethics of the Code of Conduct in the schools of Aqaba Governorate and in the Hashemite Kingdom of Jordan.
Keywords: teachers; ethics; code of conduct; obstacle; school principals